Les individus face à l’événement « cancer » - Lionel Pourtau; Agnès Dumas; Philippe Amiel (Temporalités)
In this article, we present arguments on the impact of cancer on the collective experience of time within two main social institutions, family and the workplace. This disease always provokes a biographic crisis when it appears. Nevertheless, as medical technology progresses, cancer is becoming a chronic disease, and the social effects of cancer are changing. It is no longer the same disease with a short-term risk of death. Treatments can last for years with uncertain results and induce handicap or social stigma. The collective experiences of time, shared between the sick person and her family and friends, tend to break up, entailing time breaks and leading to the social isolation of the patient. The ecliptic dimension of the disease, with its remissions and relapses, gives rise to repeated biographic crisis.